2022
DOI: 10.1186/s13071-022-05220-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of novel lab assays to examine the effect of pyrethroid-treated bed nets on blood-feeding success and longevity of highly insecticide-resistant Anopheles gambiae s.l. mosquitoes

Abstract: Background There is a pressing need to improve understanding of how insecticide resistance affects the functional performance of insecticide-treated nets (ITNs). Standard WHO insecticide resistance monitoring assays are designed for resistance surveillance and do not necessarily provide insight into how different frequencies, mechanisms or intensities of resistance affect the ability of ITNs to reduce malaria transmission. Methods The current study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…Despite low levels of mortality with the pyrethroid only Olyset Net and next-generation Interceptor G2, blood feeding success in resistant strains was reduced by up to 83% and 41% respectively. A reduction in blood-feeding following insecticide exposure was also found by Barreaux et al [ 36 ] who reported that after forced exposure to ITNs the blood feeding success of highly insecticide resistant An. gambiae strains was reduced.…”
Section: Discussionsupporting
confidence: 69%
“…Despite low levels of mortality with the pyrethroid only Olyset Net and next-generation Interceptor G2, blood feeding success in resistant strains was reduced by up to 83% and 41% respectively. A reduction in blood-feeding following insecticide exposure was also found by Barreaux et al [ 36 ] who reported that after forced exposure to ITNs the blood feeding success of highly insecticide resistant An. gambiae strains was reduced.…”
Section: Discussionsupporting
confidence: 69%
“…The results here presented provide evidence that in coastal area of Côte d’Ivoire, where malaria incidence is increasing in recent years—sleeping under a LLIN does not fully prevent being bitten by a malaria vector, and thus malaria transmission, nor the possibility for Anopheles females to digest their blood-meal indoors. This may be due to high resistance to pyrethroids, which reduces both the protective and repellent effects of LLINs, as shown in several Afrotropical settings [ 48 , 49 , 50 ], but also to behavioural changes in vector populations, such as changes in biting times, exposing humans to indoor biting before sleeping under the net or immediately upon waking up [ 21 ]. Moreover, results reveal high behavioural plasticity of An.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, blood-fed females were more tolerant of lambda-cyhalothrin than unfed females, most likely resulting from the increased production of metabolic enzymes following the blood meal, many of which would contribute to the rapid degradation of the insecticide, a phenomenon first reported recently in the African malaria vector Anopheles gambiae s.l. ( 29 ).…”
Section: Discussionmentioning
confidence: 99%